Identifikasi Penyebab Penyakit Busuk Pangkal Batang pada Jeruk - Eka Retnosari; Julinda Bendalina Dengga Henuk; Meity Suradji Sinaga (Jurnal Fitopatologi Indonesia, 2014)
One major disease of citrus is basal stem rot which may cause significant constraint on citrus production in Indonesia. Research was initiated to identify the causal agent of basal stem rot disease from 11 citrus growing areas in Indonesia. Identification of fungal pathogens was based on macroscopic and microscopic observation of morphological characters. Koch Postulate was conducted to confirm the causal agent of the disease. Two fungal pathogens, Botryodiplodia theobromae, and Phytophthora citrophthora were found associated with basal stem rot disease. B. theobromaewere isolated from all plant samples, whereas P. citrophthorawas only isolated on samples from Soe (East Nusa Tenggara). Characteristic symptoms of basal stem rot disease was developed on plants inoculated with B. theobromae and P. citrophthora; this confirmed that two fungal isolates was the causal agent of basal stem rot disease.